2022
DOI: 10.7759/cureus.26323
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to the Diagnosis of Cardiac Angiosarcoma

Abstract: We present a case of a 32-year-old female presenting with shortness of breath and increasing oxygen requirements. Further imaging discovered a large mass extending circumferentially into the pericardium, cardiac wall, and chambers, involving the anterior and middle mediastinum. Direct tissue biopsy of the mass for a diagnosis was unsafe. Therefore, advanced flow cytometric analysis for tumor marker expression of the malignant effusion was used to differentiate the mass as a vascular sarcoma, consistent with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The first cytomorphology description of cardiac angiosarcoma in pericardial fluid was reported by Randall et al 5 The cells were arranged in flat clusters, with oval to spindle-shaped irregular nuclei, unevenly distributed chromatin and wispy cytoplasm. A more recent report by Kennedy et al 3 demonstrated clusters of large epithelioid malignant angiosarcoma cells in the pericardial fluid with high N:C ratio and uneven chromatin. Chang et al 2 and Ogino et al 4 described metastatic angiosarcoma (noncardiac origin) cells in pleural effusions, both of which showed epithelioid cells in clusters.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The first cytomorphology description of cardiac angiosarcoma in pericardial fluid was reported by Randall et al 5 The cells were arranged in flat clusters, with oval to spindle-shaped irregular nuclei, unevenly distributed chromatin and wispy cytoplasm. A more recent report by Kennedy et al 3 demonstrated clusters of large epithelioid malignant angiosarcoma cells in the pericardial fluid with high N:C ratio and uneven chromatin. Chang et al 2 and Ogino et al 4 described metastatic angiosarcoma (noncardiac origin) cells in pleural effusions, both of which showed epithelioid cells in clusters.…”
Section: Discussionmentioning
confidence: 96%
“…However vast majority of cases reported in the literature showed negative pericardial fluid cytology, and initial diagnosis of primary cardiac angiosarcoma based on pericardial fluid cytology has very rarely been reported. 3,5 The most likely cause of this low sensitivity is the paucity of malignant cells in the specimens. In addition, due to the rarity of the disease seen in body fluid, cytopathologists are not familiar with the cytomorphology and likely to have low suspicion for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite advancements in non-invasive imaging modalities, which are of great value in the characterization of the mass, histopathological examination is required to establish a definitive diagnosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%